2020
DOI: 10.18805/ijar.b-1289
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Micromeria congesta Essential Oil Extract on Wound Healing in Rabbits and Molecular Genetics Applications

Abstract: Background: The chemical composition and antimicrobial and antioxidant properties of Micromeria congesta (M. congesta) have been previously revealed, but their effect on wound healing has not been investigated. This study aimed to investigate the effects of M. congesta extract in rabbits where full-thickness skin wounds were used. Methods: Twentyone New Zealand rabbits that were used in the study were divided into 3 groups as Group I (M. congesta’s essential oil extract), Group II (Centella asiatica (C. as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This is supported by the ability of CMP to reduce oxidative stress in the wound region (Ebaid et al 2011). Normally, the first type of cell migrating to the wound site is neutrophils, which eliminate microorganisms followed by their consumption by macrophages (M2), ceasing the level of inflammation at the wound site (Yavuz et al 2022). The cessation of inflammatory mediator aggression is essential for promoting the wound healing process (Ebaid et al 2015) showed that the level of TNF-α was strikingly restored to normal in DM treated with CMP.…”
Section: Keratinocyte Proliferation and Epidermal Migrationmentioning
confidence: 99%
“…This is supported by the ability of CMP to reduce oxidative stress in the wound region (Ebaid et al 2011). Normally, the first type of cell migrating to the wound site is neutrophils, which eliminate microorganisms followed by their consumption by macrophages (M2), ceasing the level of inflammation at the wound site (Yavuz et al 2022). The cessation of inflammatory mediator aggression is essential for promoting the wound healing process (Ebaid et al 2015) showed that the level of TNF-α was strikingly restored to normal in DM treated with CMP.…”
Section: Keratinocyte Proliferation and Epidermal Migrationmentioning
confidence: 99%